164k views
2 votes
5x + 2y=7
- 2x + 6y=9

User Kornero
by
6.2k points

1 Answer

3 votes

Answer:

x =
(12)/(17) or 0.706


y = (59)/(34) or 1.735

Explanation:

5x + 2y=7 ----->(eq 1)

- 2x + 6y=9 ----->(eq 2)

Multiply (eq 1) with 3

3×(5x + 2y) = 3×7

15x + 6y = 21 ----->(eq 3)

substract (eq 3) from (eq 2)

- 2x + 6y - (15x + 6y) = 9-21

- 2x + 6y - 15x - 6y = 9-21

- 2x - 15x + 6y - 6y = 9-21

-17x = -12

x = -12 ÷ -17

x =
(12)/(17)

put x =
(12)/(17) in (eq 1)


5*(12)/(17) + 2y = 7


2y = 7- 5*(12)/(17)


2y = (7*17 - 60)/(17)


2y = (119- 60)/(17)


2y = (59)/(17)


y = (59)/(17*2)


y = (59)/(34)

User Nicksrandall
by
5.2k points